Nutrient administration and resistance training - Kerksick, C. H.; Leutholtz, B. (Journal of the International Society of Sports Nutrition, 2005)
Skeletal muscle tissue is tightly regulated throughout our bodies by balancing its synthesis and breakdown. Many factors are known to exist that cause profound changes on the overall status of skeletal muscle, some of which include exercise, nutrition, hormonal influences and disease. Muscle hypertrophy results when protein synthesis is greater than protein breakdown. Resistance training is a popular form of exercise that has been shown to increase muscular strength and muscular hypertrophy. In general, resistance training causes a stimulation of protein synthesis as well as an increase in protein breakdown, resulting in a negative balance of protein. Providing nutrients, specifically amino acids, helps to stimulate protein synthesis and improve the overall net balance of protein. Strategies to increase the concentration and availability of amino acids after resistance exercise are of great interest and have been shown to effectively increase overall protein synthesis. After exercise, providing carbohydrate has been shown to mildly stimulate protein synthesis while addition of free amino acids prior to and after exercise, specifically essential amino acids, causes a rapid pronounced increase in protein synthesis as well as protein balance. Evidence exists for a dose-response relationship of infused amino acids while no specific regimen exists for optimal dosing upon ingestion. Ingestion of whole or intact protein sources (e.g., protein powders, meal-replacements) has been shown to cause similar improvements in protein balance after resistance exercise when compared to free amino acid supplements. Future research should seek to determine optimal dosing of ingested intact amino acids in addition to identifying the cellular mechanistic machinery (e.g. transcriptional and translational mechanisms) for causing the increase in protein synthesis.